Penerapan Digitalisasi Teknologi Informasi untuk Meningkatkan Kompetensi dan Karakter Siswa di SMK Mustafa Perbaungan: Pengabdian - Sri Handayani; Annas Prasetio (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This community service activity aims to implement digitalization of information technology to improve academic competence and character building of students at SMK Mustafa Perbaungan. This activity is motivated by the limited use of digital technology in learning which impacts low participation, motivation, and strengthening of student character. The implementation method includes needs analysis, planning, training and mentoring the use of digital learning media, and evaluation. Digitalization is carried out through the use of information technology-based applications that support interactive, collaborative, and fun learning by actively involving teachers and students. The results of the activity show an increase in student understanding, skills, motivation, and activeness, the formation of positive character, and increased teacher competence in designing and implementing digital learning effectively, thus contributing positively to the quality of learning and strengthening student character at SMK Mustafa Perbaungan.